Trends in age at natural menopause and menarche and related factors in Iran: results from a population-based study - Neda Bazyar; Zahra Moradi; Ali Khani Jeihooni; Azizallah Dehghan (Scientific Reports)
Abstract This study aimed to examine trends in the ages of menarche and menopause, and related factors, among women in the Fasa Cohort Study. We analyzed cross-sectional data from the Fasa cohort, part of the Persian cohort study, which included 11,000 Iranian adults aged 35 to 75, with 5311 being women. These women were categorized into four age groups: 35–44, 45–54, 55–64, and 65–75 years. We explored changes in mean ages at menarche and menopause, along with associated factors, using SPSS 22 software and applying descriptive statistics, chi-square tests, t-tests, ANOVA, and multivariable linear regression. Results indicated a reduction in mean age at menarche from 14.16 to 13.40 years and a decline in mean age at menopause from 52.27 to 40.25 years across the same age groups, both statistically significant (p < 0.001). A significant relationship was found between age at menopause and factors such as education level, marital status, hypertension, and thyroid disease (p < 0.001). Women without a history of hypertension experienced menopause 0.84 years later than those with the condition, and those without thyroid disease had a delay of 0.75 years. Additionally, each year a woman delays having her first child corresponds to a 0.11-year increase in her age at menopause.